Outcome of Image-Guided Surgical Biopsy of Brain Lesions: A Single Centre Experience. (1st October 2022) - Saleh ElGhamry, Ahmed Mohammed Nabil; Simon, Natalie; Eltayeb, Mohamed; Surash, Surash
Abstract: AIMS: The aim of this study was to quantify the accuracy of surgical biopsy for brain lesions using different image-guidance techniques, in our tertiary neurosurgical centre. METHOD: Retrospective data was collected from electronic and paper patient notes. Data collected included: age, sex, comorbidities, pre-operative functional images, surgeon grade, biopsy method, number of targets, number of samples, result from frozen section and fixed sample histopathology, complications, and length of stay. Methods of biopsy included: ultrasound-guided, frame-based biopsy and frameless Brainlab guided biopsy (free-hand, Varioguide and registration tool -guided). RESULTS: A percentage of 11.5% of cases (total = 52) were US-guided biopsy. Navigated frameless biopsies comprised 76.9% of all cases. In these cases, 42.3% of cases were guided by the registration tool, 23% used a fixed "Varioguide" instrument alignment tool and 11.5% were completed using the free-hand method. Overall accuracy of biopsy for all cases was 82.69%. Accuracy rates of different frameless methods were: 81.8% for Brainlab registration- guided biopsy, 66.7% for Brainlab Varioguide biopsy and 100% for Brainlab free-hand frameless biopsies. The percentage of complications was 5.8%. CONCLUSION: In our centre, the accuracy of image-guided surgical biopsy for brain lesions was as high as 82.69% with a low complication rate of 5.8%. The Brain lab free-hand technique had the highest diagnostic yield and safety amongst all frameless stereotactic techniques.